Smart vision: Assistive device for the visually impaired community using online computer vision service - Baskaran H.; Leng R.L.M.; Rahim F.A.; Rusli M.E. (Institute of Electrical and Electronics Engineers Inc., 2023)
Deep learning; Assistive; Assistive devices; Daily lives; On-machines; Online image processing; Prototype development; System behaviors; Visually impaired; Computer vision